ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF LEAVES, SKIN, FLESH AND SEEDS OF SRI LANKAN VARIETY OF CUCURBITA MOSCHATA (International Journal of Ayurveda and Pharma Research, 2018)
Reactive oxygen species are continuously produced by normal physiological activities of the human body and these cause damage to the cell membrane and biomolecules and thereby resulting chronic diseases. Antioxidants are scavengers of such free radicals and could combat oxidative stress. In spite of the advances in modern medicine, plant based remedies are increasingly sort after due to their lesser side effects. The antioxidants capacity and antimicrobial properties of ethyl acetate, acetone and methanol extracts of seeds, leaves, flesh and skin of the Sri Lankan variety of Cucerbita moschata were investigate. The ethyl acetate extracts of leaves gave the highest rate of change of reducing power with concentration (0.1625 ml/mg) in Fe3+ reducing power assay and the highest hydroxyl radical activity (72.8±3.8%). The acetone extract of leaves gave the highest rate of change of radical scavenging activity with concentration (7.016 ml/mg) during DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay. Ethyl acetate extract of leaves also showed the highest phenolic content (42.4±2.4 mg (PGE/g)) and highest flavonoid content (40.2±0.6 mg (QE)/g). All extracts of skin and seeds as well as the methanol extract of leaves and acetone extract of flesh showed antibacterial activity against Bacillus subtilis. The three extracts of skin and the acetone extract of leaves showed antibacterial activity against the Escherichia coli.